Division I hockey players generate more power than Division III players during on- and off-ice performance tests - Peterson, B. J.; Fitzgerald, J. S.; Dietz, C. C.; Ziegler, K. S.; Ingraham, S. J.; Baker, S. E.; Snyder, E. M. (The Journal of Strength and Conditioning Research, 2015)
Current research has found anthropometric and physiological characteristics of hockey players that are correlated to performance. These characteristics, however, have never been examined to see whether significant differences exist between on- and off-ice performance markers at different levels of play; Division I, Elite Junior, and Division III. The purpose of this study was to examine the differences that may exist between these characteristics in Division I (24), Elite Junior (10), and Division III hockey (11) players. Forty-five (age: 18-24 years) hockey players completed anthropometric, on-ice, and off-ice tests to ascertain average measures for each division of play. On-ice testing was conducted in full hockey gear and consisted of acceleration, top-speed, and on-ice repeated shift test (RST). Off-ice tests included vertical jump, Wingate, grip strength, and a graded exercise test performed on a skating treadmill to ascertain their VO2peak. Division I players had significantly lower body fat than their Division III peers (p = 0.004). Division I players also scored significantly better on measures of anaerobic power; vertical jump (p = 0.001), Wingate peak power (p = 0.05), grip strength (p = 0.008), top speed (p = 0.001), and fastest RST course time (p = 0.001) than their Division III counterparts. There was no significant difference between Division I and Elite Junior players for any on- or off-ice performance variable. The results of this study indicate that performance differences between Division I and Division III hockey players seem to be primarily because of the rate of force production.